A generalized model predictive control method for series elastic actuator driven exoskeleton robots. (September 2021) - Li, Shenghui; Shi, Ying; Hu, Linna; Sun, Zhenxing
Abstract: In order to optimize the control performance of the compliant actuator system, a generalized predictive control (GPC) method is introduced in the controller design. Compared with conventional predictive control methods which largely depend on the modeling, the proposed GPC method is almost model-free. The stability of closed-loop system has been rigidly proved. Various experimental tests of a series elastic actuator driven exoskeleton robot are verified the effectiveness of the proposed methods.